2017
DOI: 10.3389/fpsyg.2017.00575
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Tinnitus and Insomnia with Repetitive Transcranial Magnetic Stimulation and Cognitive Behavioral Therapy – a Combined Approach

Abstract: It has been estimated that up to 80% of people will experience symptoms of tinnitus over the courses of their lives, with rates of comorbid sleeping problems ranging from 50 to 77%. Because of a potential connection between tinnitus and sleep disorders as well as high rates of comorbid psychiatric disorders, interdisciplinary approaches to treatment seem to be the most efficient option. In this study, we present the case of a 53-year-old male patient, who started to experience symptoms of tinnitus at the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Neurophysiological models (Jastreboff et al, 1996 ) suggest the proposed combination as a valuable approach that would also satisfy the needs of patients. As an alternative, there are also non-invasive stimulation methods that seem to ameliorate tinnitus symptoms (for a recent case study see Richter et al, 2017 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Neurophysiological models (Jastreboff et al, 1996 ) suggest the proposed combination as a valuable approach that would also satisfy the needs of patients. As an alternative, there are also non-invasive stimulation methods that seem to ameliorate tinnitus symptoms (for a recent case study see Richter et al, 2017 ).…”
Section: Limitationsmentioning
confidence: 99%
“…The elicitation of slow waves via TMS, dependent on the dosage and administration site, can significantly increase SWA across the scalp, possibly inducing a shift to a deep sleep stage (Massimini et al, 2007). This finding paves the way for larger studies investigating the effect of rTMS on deep sleep induction, a state critical to mental and physical health (Richter et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, there are a growing number of studies supporting the efficacy of rTMS for other conditions such as insomnia, catatonia, post-traumatic stress disorder, anxiety, Parkinson's disease, tinnitus, MCI, and other diagnoses (Ladenbauer et al, 2017;Richter et al, 2017;Licht et al, 2021;Li et al, 2022;Li et al, 2022;Kan et al, 2023). Nevertheless, rTMS outcomes have also been reported as heterogeneous with studies suggesting subpopulations of fast and slow responders as well as nonresponders (O'Reardon et al, 2007;Reithler et al, 2011;Yip et al, 2017;Lefaucheur et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that chronic tinnitus may be accompanied by comorbidities such as anxiety, depression and insomnia, and can have a negative impact on sleep quality, in a sense that the increased severity of sleep disruption is associated with increased tinnitus severity [ 5 , 6 , 7 , 8 , 9 , 10 ]. In patient groups with tinnitus and chronic insomnia, high emotional distress is associated with the patient’s tinnitus [ 11 , 12 ]. Ultimately, the overall distress affects every individual experiencing insomnia and tinnitus, with women being more strongly affected by the distress than men.…”
Section: Introductionmentioning
confidence: 99%